The Sword of Damocles: Living with Neurofibromatosis Type 1 (2020)
Both as a physician and as a patient, having neurofibromatosis type 1 has been an important part of my life. In my practice as a physician and as a professor, I have tried to reflect on the reality of living with a genetic condition and how it affects the way I live and practice medicine.